PERANAN WWF (WORLD WILD FUND FOR NATURE ) DALAM UPAYA PELESTARIAN DAN PENANGGULANGAN KERUSAKAN HUTAN TAMAN NASIONAL TESSO NILO TERHADAP KELANGSUNGAN HIDUP SATWA ENDEMIK DI KABUPATEN PELALAWAN PROVINSI RIAU - Nilam Hananti; Dodi Haryono; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesia has 20 million hectares of peatlands is mainly located in Sumatra (7.2 million ha) and Borneo. Riau is a province which has the largest peat land approximately 4.044 million ha or 56.1% of the total area of peatlands in Sumatera.Indonesia is one of the countries that suffered environmental problems, such as the problem of flooding, forest encroachment, until the destruction of the National Parks in several regions in Indonesia , One of the encroached forest is Tesso Nilo National Park (TNNP) located in three districts in the province of Riau, namely Pelalawan, Kampar and Kuantan Singingi.Seeing the forest conditions are constantly degraded, the WWF (World Wild Fund For Nature). Then make efforts to urge the government to immediately produce policies that support forest conservation. According to the WWF if the destruction of peatlands in the Tesso Nilo National Park continues, then it is not Indonesia who will suffer the consequences, but the regional and global community will also feel the consequences. WWF as one of the non-profit environmental organizations in Indonesia, has a vision, mission and goals of the organization. The main purpose WWFadalah to stop and repair the environmental damage and to build a future in which humans live in harmony with the WWF alam.Upaya do is save the species diversity by promoting the preservation of the social and economic benefits to local communities in a sustainable manner.Keyword: WWF – Tesso Nilo- -Forestry